2017
DOI: 10.1016/j.diamond.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Study of cubic and hexagonal cell geometries of a 3D diamond detector with a proton micro-beam

Abstract: A detector from single crystal synthetic diamond with conducting wires has been prepared with an improved femto-second laser process. The detector was characterised with a 4.5 MeV proton micro-beam (Ruder Bosković Institute, Zagreb). The charge collection efficiency and the transient current response have been investigated with high spatial resolution. A hexagonal and square cell geometry is investigated. Both cell geometries show full charge collection at 40V bias voltage, and little charge sharing between ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Such results confirm the effectiveness of the adopted buried-columns geometry as previously predicted in [29]. In addition, compared to other solutions where either superficial metal contacts or multi-wire bonding are implemented [9,27,[29][30], the proposed laser direct-writing of contacts largely simplifies the fabrication of an all-carbon diamond-based device for beta-particles detection.…”
Section: Response To Mev Energy Electronssupporting
confidence: 82%
See 2 more Smart Citations
“…Such results confirm the effectiveness of the adopted buried-columns geometry as previously predicted in [29]. In addition, compared to other solutions where either superficial metal contacts or multi-wire bonding are implemented [9,27,[29][30], the proposed laser direct-writing of contacts largely simplifies the fabrication of an all-carbon diamond-based device for beta-particles detection.…”
Section: Response To Mev Energy Electronssupporting
confidence: 82%
“…[30], a buried columns distance d around 170 µm was preferred to maintain an adequate drift distance of charge carriers at few tens of Volts of applied bias. The rectangular face-centered cell (partially resembling a hexagonal shape [27]) adopted for the device would assure a minimized overlapping of laser-induced stressed regions mainly localized within the {111} planes [19,31], although this appears particularly important for relatively low d distance in micrometer range.…”
Section: A Materials and Detector Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, they also performed tests with photon and proton micro-beams using Ion Beam Induced Charge (IBIC) and Time Resolved Ion Beam Induced Current (TRIBIC) analysis, highlighting a complete charge collection within the explored active regions of the detector. On the same topic, M.J. Booth et al [19] reported a more complete IBIC and TRIBIC analysis. They were able to evidence a full charge collection for different geometries of 3D pillars, whereas small differences, depending on the buried-contact geometry, were found in charge sharing among neighboring cells.…”
Section: Introductionmentioning
confidence: 98%
“…Aberration correction has furthermore been transformative for writing 3D conductive graphitic wires beneath the surface of diamond, as shown in Fig. 4d 54 , where the resistivity of the wires drops by orders of magnitude when using AO, creating possibilities for the fabrication of radiation detectors 55 and components for quantum processing 5658 . Aberration correction has also been successfully applied to different fabrication strategies for laser-written fibre Bragg gratings 26,59 , three-dimensional data storage in polymers 32 , tailored edge-cleaving of glass plates 60 , and fabrication inside liquid crystal devices 61,62 .…”
Section: Implementations Of Ao In Dlwmentioning
confidence: 99%